PULAU MAYA DAN HUBUNGANNYA DENGAN SEGITIGA EMAS SUMATERA-JAWA-KALIMANTAN PADA MASA KLASIK - Herwanto, Eko (Naditira Widya, 2010)
The dynamic of social politic, economy, and culture in the golden triangle between Sumatera, Java and Kalimantan was marked by the birth of Sriwijaya, Tarumanegara, and other old kingdoms during the Indonesian Classical period. The development of Hindu-Buddhist civilization had influenced other surrounding island including groups of islands in the Karimata Strait. One of the islands which are assumed to have had great cultural impact from Sumatera, Java and Kalimantan is Maya Island. The latest research carried out in Maya Island indicated traces of Hindu-Buddhist influence in form of statues and stupa relief. Based on such evidence, it can be inferred that Maya Island played an important role in the golden triangle, which act as cultural bridge and trading transit for Sumatera, Java, and Kalimantan. This article discusses the role of Maya Island in the Indonesian Classical agenda.